Origins of the theory of legal consciousness (Journal of actual problems of jurisprudence, 2019)
Any social phenomenon as long social process has its origins education, then influencing their orientation, trends andperformance. All these aspects are revealed in this article in relation to such phenomena as law and sense of justice intwo aspects: the historical, theoretical. The historical aspect is related to the peculiarities of formation of legal awarenessin nomadic civilizations. Theoretical – with the development of the theory and the theory of law enforcement.Key words: sense of justice, common law, the social process enforcement.